Reframing ‘Primitive Huts’ from Structural to Environmental Techniques and Their New Interrelationship in the Machine Age - Eun-Ji Cho; Dolaana Khovalyg; Sung-Taeg Nam (Buildings)
This study examines ‘Primitive Huts’ in relation to the structural and environmental techniques refined by savants (e.g., architects and scholars) during the Machine Age through three types of interrelationships: separation, moderation, and integration. The first aim is to reframe the theories of ‘Primitive Huts’, shifting the focus from structural to environmental techniques across two eras—the primitive and the Machine Age. Returning to the concept of ‘Primitive Huts’ in the context of the Machine Age aims to rebuild originality. In particular, this investigation looks into how the ‘Primitive Hut’ has sought ways to address environmental challenges. The second explores how the Machine Age initially provoked the separation of ‘Primitive Huts’—structural and environmental techniques—and integration (i.e., new interrelationship) through moderation. As a result, the contributions of savants are analysed to highlight the enhanced precision, discipline, and efficiency that have evolved since the Industrial Revolution.